The knowledge management requirements for the transfer of a stroke patient - Ellingham, Brett (Cranfield University, 2009)
Health care is characterised by complexity, in terms of structure and number of individuals, teams & autonomous local organisations involved in the delivery of care. An obvious requirement in maintaining continuity for the patient is knowledge transferred between these groups. An example of this is the transfer of a stroke patient from one setting for their acute care to another for their rehabilitation. Objectives of the research were within the context of a stroke patient transfer, to determine the knowledge management needs of the receiving community hospital team, provision of knowledge from the acute hospital team, shortcomings emanating from the current state and solutions for future better ways of working. Research took the form of an exploratory case study involving semi-structured interviews with clinicians involved in specialist stroke care. Findings showed that Knowledge Management is one of a number of management issues facing stroke care for the organisations studied, though currently not the most pressing. Operational, rather than clinical knowledge showed most scope for improvement. Current practises rely heavily on knowledge transfer by people, which was deemed appropriate in most cases. The research provides an insight into knowledge management within health care at an operational level, specifically applied to stroke and patient transfers; examples of which could provide insight for other specific events in a patient’s journey. Practically, conclusions could be used to guide ongoing improvement to process development for the acute and community hospital teams studied, as well as provide lessons for the opening of further community hospital stroke units.
Keywords: autonomous local organisations; acute care; rehabilitation; acute hospital team; Operational knowledge; patient transfers